2016
DOI: 10.1515/fhep-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

The ACA: Impacts on Health, Access, and Employment

Abstract: On March 23, 2010, President Barack Obama signed the Patient Protection and Affordable Care Act (ACA) into law. This comprehensive health care reform legislation sought to expand health care coverage to millions of Americans, control health care costs, and improve the overall quality of the health care system. The ACA required that all US citizens and legal residents have qualifying health insurance by 2014. In this paper we give readers a brief overview of the effects of the ACA based on recent research. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…A multivariate logistic regression model was employed, adjusting for age, race, sex, median household income and Affordable Care Act Medicaid Expansion (ACAME) enactment in 2014. The expansion of Medicaid provides health insurance to those under 65 with incomes up to 133% of the US federal poverty level [ 30 ]. In the sensitivity analysis, an interaction term was incorporated into the multivariate logistic regression model to evaluate if insurance status influenced the relationship between race and outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…A multivariate logistic regression model was employed, adjusting for age, race, sex, median household income and Affordable Care Act Medicaid Expansion (ACAME) enactment in 2014. The expansion of Medicaid provides health insurance to those under 65 with incomes up to 133% of the US federal poverty level [ 30 ]. In the sensitivity analysis, an interaction term was incorporated into the multivariate logistic regression model to evaluate if insurance status influenced the relationship between race and outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…117 Additionally, many communities globally affected by communicable diseases such as neglected tropical diseases (NTDs) are of low socioeconomic status and lack access to health services. 118 Studies have shown that expanding health coverage decreases health disparities, 119 , 120 and it is likely that health disparities are lower in settings with universal access to health care compared to settings that lack health care access for all.…”
Section: Social Determinants Of Health and Fungal Infectionsmentioning
confidence: 99%
“…However, a 2012 US Supreme Court ruling granted individual states the authority to decide whether to adopt this provision. 6 As of February 28, 2023, 40 of the 50 US states, along with the District of Columbia (DC), have enacted Medicaid Expansion . 7 In-hospital mortality due to trauma, which is sensitive to the timeliness of care, external factors, and resource availability, serves as a metric for assessing the effectiveness of healthcare interventions, the performance of healthcare facilities, and healthcare policies.…”
Section: Introductionmentioning
confidence: 99%
“…However, a 2012 US Supreme Court ruling granted individual states the authority to decide whether to adopt this provision. 6 As of February 28, 2023, 40 of the 50 US states, along with the District of Columbia (DC), have enacted Medicaid Expansion . 7…”
Section: Introductionmentioning
confidence: 99%